The relationship between risk-taking propensity and demographic characteristics among MSEs in Malaysia - Fauzilah Salleh; Mohamed Dahlan Ibrahim (Inderscience Publishers, 2013)
Micro- and Small Enterprises (MSEs) contribute significantly to economic development, and this could be influenced by demographic factors and risk-taking propensity. This study assesses the relationship between risks-taking propensity and demographic characteristics of Malaysian MSEs owners. A stratified sample totalling 260 names and addresses was derived from the Small and Medium Industries Development Corporation (SME Corp). The Risk Attitudes Inventory (RAI) was used in the survey to measure entrepreneurial risk-taking propensity, which presented with 15 hypothetical situations. The questions were to stimulate reflection and thought about one’s risk-taking style and beliefs. The scale that was used for the measurement of risk-taking propensity consisted of three levels: low, medium and high. The study concludes that there is no relationship between risk-taking propensity and business owners’ demographic characteristics such as gender, business owners’ age, education level and their business experience.